Genome-wide identification of cytokinin oxidase family members in common bean (Phaseolus vulgaris): identification, phylogeny, expansion, and expression pattern analyses at the sprout stage under abiotic stress - Zhang, Q.; Wang, S.; Xu, J.; Zhao, W.; Yang, Y.; Wang, L.; Du, Y.
Common bean (Phaseolus vulgaris), a crop with high economic value, is sensitive to abiotic stress. Cytokinins play a crucial role in promoting plant growth and metabolism. Cytokinin oxidase (CKX)family members have been identified and analyzed in some plants; however, such investigations have not been conducted in common beans. Here, CKX family members of the common bean were identified, and a comprehensive analysis was performed on these members. In this study, ten members of PvCKX (CKX members in common bean)were identified, their respective locations were drawn on five chromosomes, and five subgroups were identified through phylogenetic analysis of CKX members in Arabidopsis, rice, maize, soybean, and common bean. A comprehensive analysis of PvCKXs revealed that the members in the same subgroup had similar motifs, gene structure, and cis-regulatory elements, while some members contained hormones, stress- and regulation-related elements, and gene ontology (GO)and Kyoto encyclopedia of genes and genomes (KEGG)enrichment analyses were performed to predict the function of hormone-related PvCKXs, in which family members exercise through hormones, especially zeatin. The expression patterns of PvCKXs in different tissues and their responses to abiotic stress at the sprout stage using Phytozome database and quantitative real-time PCR (qRT-PCR)revealed variations, revealing that PvCKXs respond to abiotic stresses and have connection with CKX activity and zeatin content. The results of PvCKXs' characteristics revealed that PvCKXs regulate CKX activity and zeatin content and then respond to abiotic stresses, providing a basis for further analysis of PvCKXs in common beans.
Keywords: CYTOKININ OXIDASE (CKX)FAMILY; COMMON BEAN (PHASEOLUS VULGARIS); IDENTIFICATION; EXPRESSION PATTERN; SPROUT STAGE; ABIOTIC STRESS